1991
DOI: 10.3347/kjp.1991.29.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Enterobius vermicularis infection and preventive effects of mass treatment among children in rural and urban areas, and children in orphanages

Abstract: An epidemiological study and mass treatments of Enterobius vermicularis infection among children near Wonju area of Kangwon province were carried out. The children were divided into 4 groups according to their residing localities; children in the mountainous area, rural area, urban area and in orphanage. They were examined by adhesive cellotape anal swab technique, and egg positive rates were obtained. The rates of egg reduction and re-infection rates after repeated mass treatments were also observed. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
1
15
1
Order By: Relevance
“…18.5%) of E. vermicularis infection among children attending kindergartens and primary schools on the western and southern islands of the Republic of Korea. This prevalence is higher than those reported by other workers (7.8-17.5%) since 1991 in the Republic of Korea (Kim et al, 1991;Yang et al, 1997;Lee et al, 2000;Yoon et al, 2000, and is remarkably higher than the national fig It is of note that the detection of E. vermicularis eggs from the peri-anal region means the termination of parasitism by the adult worms that produced these eggs (Akagi, 1973;Cho and Kang, 1975), and that such a finding does not necessarily mean that further worms are present in the intestine. Nevertheless, egg detection from the perianal region is significant, because egg positivity indicates a high probability of infection in the intestine (Cho and Kang, 1975).…”
Section: Discussioncontrasting
confidence: 55%
“…18.5%) of E. vermicularis infection among children attending kindergartens and primary schools on the western and southern islands of the Republic of Korea. This prevalence is higher than those reported by other workers (7.8-17.5%) since 1991 in the Republic of Korea (Kim et al, 1991;Yang et al, 1997;Lee et al, 2000;Yoon et al, 2000, and is remarkably higher than the national fig It is of note that the detection of E. vermicularis eggs from the peri-anal region means the termination of parasitism by the adult worms that produced these eggs (Akagi, 1973;Cho and Kang, 1975), and that such a finding does not necessarily mean that further worms are present in the intestine. Nevertheless, egg detection from the perianal region is significant, because egg positivity indicates a high probability of infection in the intestine (Cho and Kang, 1975).…”
Section: Discussioncontrasting
confidence: 55%
“…Of the 7,048 children examined, 4.0% were found to be positive for E. vermicularis eggs; this value was lower compared to the EPR observed in other cities such as 7.9% in Cheongju [8], 10.7% in Busan [10], and 28.4% in Wonju-si [11]. Analysis by region revealed that the EPR was the highest in Chuncheon-si (5.7%), followed by Inje-gun (4.6%) and Paju-si (3.5%) (Table 1).…”
mentioning
confidence: 78%
“…Routine stool examination methods, such as formalin-ether concentration method and cellophane thick smear, showed that the E. vermicularis infection rate to be 0.1% among the inhabitants in the upper stream of Kumgang (River) and 0.02% among the patients who had visited Seoul Paik Hosptial (Kim et al, 1994;Lee et al, 1994 (Kim et al, 1991). Since the life cycle of the parasite and children's habits affect the control of E. vermicularis, a strict control or extermination of enterobiasis is difficult.…”
mentioning
confidence: 99%